Approaches to coral reef restoration in a changing climate – identifying objectives behind a sea of options - Gong, Charlie (SLU/Dept. Of Aquatic Resources, 2020)
Traditionally, researchers have strived to intervene as little as possible when restoring coral reefs, to avoid risks and let the ecosystem recover naturally. But at present time, those restoration options are often insufficient due to the increasing impacts of climate change. Some researchers have therefore turned to intensive options that risk changing the natural ecosystem. It is, however, not clear if the paradigm is shifting and if restorations are commonly tailored to tolerate the predicted future climate changes. Terrestrial systems are facing the same issues and a typology has recently been created to organize terrestrial restoration options and to put them into a climate change context. The aim of this thesis is to identify objectives and motivations behind restoration options for coral reefs, by using this typology. A broad literature search was done to include various types of active restoration options. Manual selection generated 55 unique studies from the last 10 years. Among these, 26 restoration options were identified and 25 of them were organized using the typology. Low intensity options, assisting the ecosystem to recover naturally without much intervention were more commonly used than highly intensive, more intrusive options, suggesting that a paradigm shift has not yet occurred in practice. High costs and other logistical factors might explain these results where researchers may be forced to use low intensity options, even if they believe highly intensive options are needed.